A COLABORAÇÃO DO SEGMENTO PRIVADO DA EDUCAÇÃO SUPERIOR NA PROPOSTA DE DEMOCRATIZAÇÃO DO ACESSO: UM ESTUDO DA PERSPECTIVA SUL CATARINESE - Thiago Henrique Almino Francisco (Universidade Federal de Santa Catarina, 2014)
Considering the democratization of access to higher education, the article aims to present what are the main contributions of Colleges Isolated located in the southern state of Santa Catarina. Therefore, the theoretical contributions are structured under the aegis of a reflection based on the evolution of higher education in Brazil, reflections on the quality in the segment and the PNE as a guiding instrument of expansion of higher education. Thus, based on methodological guidelines, the research is characterized as being predominantly qualitative, with its main bases centered on a case study of HEIs located in the southern state of Santa Catarina. The results allow us to conclude that the main indicators that practices related to compliance with the characteristics of the social surroundings allow align academic and administrative actions that promote democratization of access, equity and retention, fostering opportunities for achieving the objectives of the National Plan of Education.